Analysis of Sentence Errors in Fiction Text Essays Theme 8 Class V MI Al-Iman Bulus School Year 2021/2022 - Syati Antika Asna; Bagiya Bagiya; Muflikhul Khaq (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This study aims to describe several errors in sentences, namely (1) errors in the use of periods, (2) errors in the use of sentence structures, (3) errors in the use of prepositions, and (4) errors in the use of parent sentences and subsentences in class V MI fiction text essays. This study uses qualitative research methods with qualitative descriptive research types. The subjects of the study were students of class V MI Al-Iman Bulus. Data collection techniques use observation and documentation. Data collection in this study used an interactive model from Miles and Huberman, namely, data collection, data reduction, data presentation, and drawing conclusions. The results showed that the total number of sentence writing errors was 200. 96 errors in the use of periods with an error percentage of 48%, 42 errors in the use of sentence structures with an error percentage of 21%, 30 errors in the use of prepositions with an error percentage of 15% and 32 errors in the use of parent sentences and children with an error percentage of 16%.